The effects of second-alloying-element on the formability of Mg-Sn alloys in respect of the stacking fault energies of slip systems. (December 2021) - Cheng, Xiongying; Yuan, Yuan; Chen, Tao; Zheng, Zebang; Ma, Lifeng; Jiang, Bin; Tang, Aitao; Pan, Fusheng
Abstract: Generalized stacking fault (GSF) energies of the basal 0001 11 2 ̅ 0 ，prismatic 10 1 ̅ 0 11 2 ̅ 0 and pyramidal 11 2 ̅ 2 11 2 ̅ 3 slip systems in the primary phase of Mg-Sn based-alloys have been studied using first-principles calculations in this work, where twenty-one third elements (X) have been taken in to consideration for their solution in primary (Mg, Sn) phase. The relative positions of Sn and X in Mg142 Sn1 X1 supercell have been determined by searching the minimum formation energies points. It is shown that, with alloying-elements of Sn and X, the unstable stacking fault energy ( γ us ) of the basal and prismatic slip systems are decreased compared with that of Mg144 . For the pyramidal slip system, only certain second-alloying-elements, namely Ag, Al, Cd, Ga, In, Li and Zn, soluted into the Mg-Sn alloys, make the γ us lower than that of pure Mg. The atomic radius of element X has a significant impact on the γ us value of Mg142 Sn1 X1, and also indirectly affects the γ us by affecting the relative substitution positions of Sn and X atoms in the structure. Accordingly, the plastic formability parameters χ have been analyzed based on the calculated stacking fault energy (SFE) values. The effects of second-alloying-elements on GSF energies and χ provide a guidance for the design of high-performance multi-elements-alloying Mg alloys.